RRM1, RRM2 and ERCC2 Gene Polymorphisms in Coronary Artery Disease - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2016)
Background/Aim: Coronary artery disease (CAD) is a chronic inflammatory disease seen as formation of atherosclerotic plaques (atheroma) in coronary arteries. Recent published papers show that DNA damage and repair mechanisms play a crucial role on the development and severity of atheromas. In this study, we investigated nucleotide excision repair (NER) pathway-related gene polymorphisms in atherosclerosis. XPD, encoded by ERCC2 gene, is an ATP-depended helicase enzyme involved in the NER pathway. Ribonucleotide reductase (RR) is a tetrameric enzyme, synthesizing deoxyribonucleotides from ribonucleotides for DNA synthesis. RR is encoded by the RRM1 and RRM2 genes, which are two subunits of RR enzyme. Materials and Methods: DNA samples isolated from peripheral blood were genotyped with real-time polymerase chain reaction (RT-PCR) for RRM1 (rs12806698), RRM2(rs6859180) and ERCC2 (rs13181) genes. Results: The frequency of the RRM1 AC heterozygote genotype was found to be significantly lower (odds ratio (OR) = 0.369, 95% confidence interval (CI) = 0.179-0.760; p = 0.006), whereas the CC homozygote genotype was found to be significantly higher in patients compared to controls (OR = 7.636, 95% CI = 2.747-21.229; p = 0.000). In addition, the RRM1 A allele was higher in control group (p = 0.000, OR = 0.131 95% CI = 0.047-0.364). For the ERCC2 gene, GG genotype was significantly higher in control group (p = 0.017, OR = 0.387, 95%CI = 0.175-0.152) and TT genotype (p = 0.021) was higher in CAD group. TT genotype had a similar to 3-fold increased risk (OR = 3.615, 95%CI = 1.148-11.380) for CAD. Carrying T allele appears to be a risk factor for CAD (p = 0.017, OR = 2.586, 95%CI = 1.173-5.699), while the G allele might be a risk-reducing factor (p = 0.021, OR = 0.277, 95%CI = 0.088-0.871) for CAD. Conclusion: RRM1 and ERCC gene polymorphisms, having homozygous mutant genotype, might be a risk factor for CAD. RRM1 and ERCC wild type alleles are risk-reducing factor for CAD. Also, carrying RRM1 A allele might have a protective effect for smokers.
Keywords: RRM1; RRM2; ERCC2; polymorphism; CAD; NUCLEOTIDE EXCISION-REPAIR; DNA-REPAIR; ASSOCIATION; CANCER; RISK